Strategi Pemanfaatan Instagram @serambilirboyo Terhadap Perkembangan Dakwah Di Era New Media - Adila, Citra; Aeni, Delliana Fitri; Alfais, Muhammad Danil Fatih; Shafrani, Kharisma (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2023)
The strategy of using Instagram as a propaganda medium is now widely used, one of which is the Instagram account @serambilirboyo. The era of new media that is increasingly developing makes social media used by da'wah actors. This study aims to find out how the strategy carried out by the Instagram account @serambilirboyo uses Instagram to preach in the new media era. This research was conducted on the Instagram account @serambilirboyo, which is an Instagram account belonging to alumni of the Lirboyo students. This study uses a descriptive research method with a qualitative approach. Retrieval of data in this research is by interviewing and data from Instagram posts @serambilirboyo. The results of this study indicate that the da'wah strategy is carried out using photo designs and short videos.